Pembelajaran Cuci Tangan Tujuh Langkah Melalui Metode Demonstrasi pada Anak Usia Dini - Padila Padila; Juli Andri; Harsismanto J; Muhammad Bagus Andrianto; Rengga Depri Admaja (Journal of Telenursing (JOTING), 2020)
This study aims to find a website that strives to wash the hands seven of the early childhood school children in Aisyiyah 1 Kindergarten, Bengkulu City. The research design used a pre-experimental method with one group pretest-posttest. The results showed that before the intervention was given the first-star category, there were 27 people (90%). The children got the second-star sort as many as three people (10%), while the number of respondents after being given the intervention experienced an increase in ability and the third-star category was seven people ( 23.3%) and get IV stars as many as 23 people (76.7%), and the bivariate analysis using the Wilcoxon test obtained p-value = 0.000. In conclusion, there is a significant influence between the method of increasing the handwashing ability of seven early childhood in Aisyiyah 1 Kindergarten, Bengkulu City. Keywords: Hand washing, Demonstration Method, Early Age